(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
Cancer has traditionally been viewed as a genetic disease caused by the sequential accumulation of mutations in oncogenes and tumor suppressor genes. However, the literature increasingly shows a significant paradigm shift: oncogenesis is now understood as a complex, multilevel process in which metabolic and epigenetic disturbances may play a role that is at least as important as, and potentially more primary than, genetic alterations. This article provides a comprehensive analysis of modern views on the biochemical mechanisms of carcinogenesis. It examines the limitations of the classical mutation theory, discusses metabolic reprogramming in detail, including the Warburg effect and its modern interpretation, and considers the roles of reactive oxygen species, oncometabolites, environmental factors such as heavy metals, and the clinical prospects of targeted therapy. Special attention is given to the critical relationship among the genome, epigenome, and metabolome, the disruption of which underlies malignant transformation.